The implementation of fuzzy logic controller for defining the ranking function on Malay text corpus - Bin Rodzman S.B.; Ismail N.K.; Rahman N.A.; Nor Z.M. (Institute of Electrical and Electronics Engineers Inc., 2024)
Indexed by SCOPUS